2018
DOI: 10.1152/japplphysiol.01084.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mito-Tempo prevents nicotine-induced exacerbation of ischemic brain damage

Abstract: Nicotine may contribute to the pathogenesis of cerebrovascular disease via the generation of reactive oxygen species (ROS). Overproduction of ROS leads to brain damage by intensifying postischemic inflammation. Our goal was to determine the effect of Mito-Tempo, a mitochondria-targeted antioxidant, on ischemic brain damage and postischemic inflammation during chronic exposure to nicotine. Male Sprague-Dawley rats were divided into four groups: control, nicotine, Mito-Tempo-treated control, and Mito-Tempo-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
(74 reference statements)
0
11
0
Order By: Relevance
“…93 ROS generation is the initial step in brain damage after cerebral ischemia/reperfusion. 115 ROS induce oxidative stress by activating several signaling pathways and react with and cause damage to lipids, proteins, and DNA. 116,117 Nicotinamide adenine dinucleotide (NAD) and NAD phosphate (NADP) are essential for maintaining the intracellular balance between the generation of ROS (which ensures a reductive environment for cellular activities) and neutralization (which maintains energy homeostasis).…”
Section: Ischemic Strokementioning
confidence: 99%
“…93 ROS generation is the initial step in brain damage after cerebral ischemia/reperfusion. 115 ROS induce oxidative stress by activating several signaling pathways and react with and cause damage to lipids, proteins, and DNA. 116,117 Nicotinamide adenine dinucleotide (NAD) and NAD phosphate (NADP) are essential for maintaining the intracellular balance between the generation of ROS (which ensures a reductive environment for cellular activities) and neutralization (which maintains energy homeostasis).…”
Section: Ischemic Strokementioning
confidence: 99%
“…It has been reported that mito‐T is a potent mitochondria‐targeted antioxidant, which could act in ischemic tissues linked with hypoxia‐induced oxidative stress (Ding, Liu, Bi, & Zhang, 2017; Du et al, 2019; Du, Farhood, & Jaeschke, 2017; Li et al, 2018; Liu, Wang, Ding, & Wang, 2018; Nautiyal, Shaltout, Chappell, & Diz, 2019; Shetty, Kumar, & Bharati, 2019; Yang et al, 2018; Zhan et al, 2018). In the present study, mito‐T, a mitochondria‐targeted superoxide dismutase mimetic, dramatically reduced AMA‐induced mitochondrial oxidative stress, and thus effectively protected MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mito-T is a potent mitochondriatargeted antioxidant, which could act in ischemic tissues linked with hypoxia-induced oxidative stress (Ding, Liu, Bi, & Zhang, 2017;Du et al, 2019;Du, Farhood, & Jaeschke, 2017;Li et al, 2018;Liu, Wang, Ding, & Wang, 2018;Nautiyal, Shaltout, Chappell, & Diz, 2019;Shetty, Kumar, & Bharati, 2019;Yang et al, 2018;Zhan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Group 3 (L-Arginine +Mito-TEMPO treated) received 0.7mg/kg body weight/ day, i.p. for 7 days started 24 hours after L-arginine injection 27,28 .…”
Section: Experimental Designmentioning
confidence: 99%
“…The tempo is a mimetic superoxide dismutase that in the catalytic cycle dismutases superoxide, while TPP is a membrane-permeant cation that accumulates several hundred folds inside the membrane potential driven mitochondria. This combination produces an effect-targeted mitochondrial chemical 26,27 .…”
Section: Introductionmentioning
confidence: 99%